Long-term Periodicities of Cataclysmic Variables with Synoptic Surveys. (20th July 2017) - Yang, Michael Ting-Chang; Chou, Yi; Ngeow, Chow-Choong; Hu, Chin-Ping; Su, Yi-Hao; Prince, Thomas A.; Kulkarni, Shrinivas R.; Levitan, David; Laher, Russ; Surace, Jason; Drake, Andrew J.; Djorgovski, Stanislav G.; et al.
Abstract: A systematic study on the long-term periodicities of known Galactic cataclysmic variables (CVs) was conducted. Among 1580 known CVs, 344 sources were matched and extracted from the Palomar Transient Factory (PTF) data repository. The PTF light curves were combined with the Catalina Real-Time Transient Survey (CRTS) light curves and analyzed. Ten targets were found to exhibit long-term periodic variability, which is not frequently observed in the CV systems. These long-term variations are possibly caused by various mechanisms, such as the precession of the accretion disk, hierarchical triple star system, magnetic field change of the companion star, and other possible mechanisms. We discuss the possible mechanisms in this study. If the long-term period is less than several tens of days, the disk precession period scenario is favored. However, the hierarchical triple star system or the variations in magnetic field strengths are most likely the predominant mechanisms for longer periods.